La gestion urbaine des années Lula. Le drainage comme enjeu du développement urbain durable à Recife - Fabiano Rocha Diniz (Cahiers des Amériques Latines)
Electing Lula in 2002 brought to Brazilians a hope of better life conditions to the poorest population. In this paper, we try to contribute to the knowledge of public action’s evolution as an answer to that hope. Knowing the connections between unequal distribution of benefits of the national development and the human habitat’s conditions in the cities, we search the tracks of the transformations in the urban and sanitation policies. Through a diachronic approach, we analyze the correlation between the evolution of the actions in these two fields and its relation with the predominant concepts of development in each studied period. At the moment the notion of sustainable development emerges, a particular aspect is studied for its transversal influence on these politics: the rain water management. In the North-east of Brazil, the poorest region of the country, the analysis of this element may allows us to apprehend the contributions of Lula’s government on building «sustainable cities».